Relations between politics and administration in the process of creating civil service in Poland. The perspective of New Institutionalism - Gadowska, Kaja (Journal of Public Governance, 2018)
Civil service is an important element in the system of public administration and has a major impact on a state’s manner of functioning. The creation of civil service in Poland was intended to ensure that the public administration performed its duties in a professional and impartial manner, unhindered by special political interests. The aim of the paper is to analyze the process of creating civil service in Poland after 1989, and to show how, in practice, from the beginning of the transformation and under the governments of successive political groups, a division was formed between the political and administrative spheres, and to what degree the actual relations between politics and public administration ref lect the formal regulations contained in civil service acts. The paper concentrates in particular on personnel policy in regard to senior positions in civil service, because these appointments are connected with assuming control of decision making processes and human resource policy in administrative offices. In the research, various complementary qualitative and quantitative methods were used. Multidimensional analysis of the data leads to the conclusion that political parties in Poland strive to limit the autonomy of the government administration and to make it subordinate to their interests. The legislation in the area of civil service has been largely subjugated to the political interest of the moment, and not to the long-term interest of the state. The use of neo-institutional perspective helps to identify the reasons behind the adoption of specific legal measures and to show their actual effects.